Case Report: Dual molecular diagnosis of gain-of-function STAT1 mutation and regulatory STAT3 variant in a patient with a hyper-IgE-like phenotype - Yaakoubi, Roukaya; Mekki, Najla; Ben Chehida, Amel; Benhammadi, Ansem; Chan, Koon-Wing; Leung, Daniel; Gharsallah, Charfeddine; Guerfali, Fatma Zahra; Barbouche, Mohamed-Ridha; Lau, Yu Lung; Ben-Ali, Meriem; Ben-Mustapha, Imen (Frontiers in Immunology, 2025)
BackgroundThe transcription factors signal transducer and activator of transcription 1 and 3 (STAT1 and STAT3) play essential roles in immune and non-immune cell function. The clinical characterization of patients carrying germline gain or loss-of-function (GOF or LOF) mutations in these genes has significantly improved our understanding of their physiological and pathological roles. Although patients with STAT3 LOF, STAT3 GOF, and STAT1 GOF mutations are classified into distinct inborn errors of immunity (IEI) categories, namely Hyper-IgE Syndrome, Regulatory T cell defects, and predisposition to Mucocutaneous Candidiasis, respectively, there is notable clinical overlap among these disorders.Case summaryWe describe a 17-year-old girl with recurrent lung infection leading to bronchiectasis, chronic onychomycosis, recurrent vulvovaginal candidiasis, and oral thrush. Additional findings included short stature, delayed puberty, and retained primary teeth. Laboratory results revealed eosinophilia and elevated IgE serum levels, with a NIH HIES score of 53. A rare heterozygous deletion within the 3′UTR of the STAT3 gene (c.*351_*353del) was identified through a candidate gene approach. Although the variant is in a non-coding region, increased STAT3 phosphorylation and elevated suppressor of cytokine signaling 3 (SOCS3) expressions suggested a potential GOF effect. In silico analysis further predicted that the deletion disrupts microRNA (miRNA) binding sites and RNA binding proteins (RBP), potentially impairing post-transcriptional regulation and contributing to STAT3 overexpression. Given the complexity of the phenotype and the atypical location of the STAT3 variation, whole-exome sequencing (WES) was performed, revealing a heterozygous missense mutation in the STAT1 DNA-binding domain (c.1053G>T, p.L351F), previously reported in autosomal dominant chronic mucocutaneous candidiasis (AD-CMC). Functional assays on lymphocytes confirmed an increased STAT1 phosphorylation compared to both STAT1 LOF patient and healthy controls.ConclusionThis case highlights the diagnostic complexity of overlapping IEI phenotypes and the value of combining targeted and WES strategies. This dual molecular diagnosis, comprising a regulatory variant in STAT3 and a pathogenic coding mutation in STAT1, emphasizes the need to include non-coding regions in genetic analyses. It also underscores the value of using techniques that offer a broader genomic view and capture all coding exons, enabling a more comprehensive correlation with the clinical and immunological phenotype.